The Effect of Jigsaw Cooperative Learning on Islamic Education Motivation Among 11th Grade Students at SMAN 12 Makassar - Makbul, M.; Ferianto, Ferianto; Farida, Nur Aini; Khayrun, M.; Sudirman, Sudirman (Proceeding International Conference on Religion, Science and Education, 2025)
This study aims to examine the effect of Jigsaw Cooperative Learning on the learning motivation of 10th-grade students in Islamic Religious Education subjects at SMAN 12 Makassar. This study is descriptive quantitative research with a survey approach that aims to describe the effect of implementing the Jigsaw cooperative learning method on students' motivation in Islamic Religious Education (PAI) subjects in class XI SMAN 12 Makassar. The population of this study was all students of class XI who had participated in learning with the Jigsaw method, with a sample of 38 students taken by purposive sampling. Two main instruments were used in data collection to measure the learning process a queue: a questionnaire on the implementation of the Jigsaw method and a questionnaire on learning motivation filled out by students; the data collected was then analyzed descriptively to describe the implementation of the Jigsaw method and how this method affects students' learning motivation. In addition, correlation analysis was also used to see the relationship between implementing the Jigsaw method and the level of student motivation. The results of this study are expected to provide a clear picture of the Effect of Jigsaw cooperative learning on students' learning motivation in class XI SMAN 12 Makassar. Jigsaw Learning Method, 53% of respondents are in the "moderate" category (values 39.39 to 47.81), 29% of respondents are in the "high" category (above 47.81), and 18% are in the "low" category (less than 39.39). Thus, most students have assessments that are around the average, with a distribution centred on the moderate category. The average motivation value of 61.24 with a standard deviation of 4.82 indicates a relatively good level of motivation. As many as 55% of respondents have learning motivation in the moderate category (57.03 to 65.43), while 18% are in the high category, and 26% are in the low category. Most respondents are in the moderate category, indicating relatively stable learning motivation. The descriptive analysis shows that the jigsaw learning method and student learning motivation are pretty good and consistent, with most students performing moderately. Implementing the Jigsaw type of cooperative learning method has a significant impact on increasing student learning motivation, especially at SMAN 12 Makassar in the subject of Islamic Religious Education (PAI). Based on the statistical analysis, this method has been proven to substantially increase learning motivation, where each increase in the implementation of the Jigsaw method increases student learning motivation by 0.849 units. In addition, this method is also effective in involving students more actively in the learning process, deepening understanding of the material, and improving social skills such as communication and collaboration. This study confirms that Jigsaw is an effective learning strategy that can improve motivation and learning outcomes in classrooms with diverse students.